The Evaluation Of Pesantren Mu'adalah Program By Using The Responsive Model In Pesantren (Islamic Boarding School) Tremas Pacitan - Mohammad Muslih; Ihwan Mahmudi; Samsirin Samsirin (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
The conferment of Mu'adalah Islamic boarding school status with Madrasah Aliyah in 2002 which was later strengthened by Law number 20 of 2003 concerning the National Education System, had a direct impact on pesantren which officially succeeded in becoming the National Education sub-system. This study aimed to evaluate the implementation of the mu'adalah program at Madrasah Aliyah Salafiyah Mu'adalah Tremas. In particular, it determines the program from the aspects of input (antecedents), processes (transactions), and program outcomes (outcomes). The evaluation used a responsive model with five stages,formulating : problem issues, identifying the data, making observation designs on inputs, activitiy process as well as results or outputs from programs, analyzing information and compiling reports. Observation design to observe antecedent, transaction and outcome, using countanance paper developed by Stake. The results of the evaluation showed that in general the success rate of the mu'adalah program at Madrasah Aliyah Salafiyah Mu'adalah Tremas is in the very good category (95.32%), with the details of the success rate on antecedent component (91.51%), transaction (94, 45%), and outcomes (100%).